Keepers of the Night Stories - Goebel, Janna (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2022)
This paper, which I presented at the Responding to Ecological Challenges with/in Contemporary Childhoods Colloquium in January 2020, is an extension of my dissertation research with children and the more-than-human world in Brazil. Drawing on Donna Haraway’s work and inspired by Karen Barad’s framing of diffraction, I take an ecofeminist, common worlds approach to my study of how children learn through becoming-with more-than-human worlds. You are invited to join in our stories and become-with us as, together, we follow provocations in different directions across time and space and speculate “and ifs.”